Neurologic Examination Findings Associated With Small Cerebellar Volumes After Prematurity. (September 2019) - Tam, Emily W.Y.; Chau, Vann; Lavoie, Raphaël; Chakravarty, M. Mallar; Guo, Ting; Synnes, Anne; Zwicker, Jill; Grunau, Ruth; Miller, Steven P.
To help clinicians understand what to expect from small cerebellar volumes after prematurity, this study aims to characterize the specific impacts of small cerebellar volumes on the infant neurologic examination. A prospective cohort of preterm newborns (<32 weeks' gestational age) had brain magnetic resonance imaging (MRI) studies at term-equivalent age. Cerebellar volumes were compared with neurologic examination findings in follow-up, adjusting for severity of intraventricular hemorrhage, white matter injury, and cerebellar hemorrhage. Deformation-based analyses delineated regional morphometric differences in the cerebellum associated with these findings. Of 119 infants with MRI scans, 109 (92%) had follow-up at 19.0±1.7 months corrected age. Smaller cerebellar volume at term was associated with increased odds of truncal hypotonia, postural instability on standing, and patellar hyperreflexia ( P < .03). Small cerebellar volume defined as <19 cm 3 by 40 weeks was associated with 7.5-fold increased odds of truncal hypotonia ( P < .001), 8.9-fold odds postural instability ( P < .001), and 9.7-fold odds of patellar hyperreflexia ( P < .001). Voxel-based deformation-based morphometry showed postural instability associated with paravermian regions. Small cerebellar volume is associated with specific abnormalities on neurologic examination by 18 months of age, including truncal tone, reflexes, and postural stability.